A virada informacional na Filosofia: alguma novidade para o estudo da mente? - Gonzalez, Maria Eunice Quilici [UNESP]; Broens, Mariana Cláudia [UNESP]; Moraes, João Antonio de [UNESP] (My University, 2010)
The concept of information is analyzed starting from Adams’ hypothesis in The Informational Turn in Philosophy, according to which there has been a far-reaching turn in Philosophy following the publication of Turing’s article “Computing Machinery and Intelligence”. Adams maintains that new guidelines are being indicated in philosophical research, having the concept of “information” as the basis for treatment of classical problems, such as the relationships between mind-body, perception-action, and the nature of knowledge, amongst others. Partially agreeing with Adams, we believe, however, that his hypothesis faces difficulties, the most fundamental of which concerns the different meanings given to the concept of information. We argue that even though the concept of information underlying the mechanicist proposal of Turing, according to which “to think is to compute”, is indeed being employed in Philosophy, this is not because of its mechanistic nature, but mainly due to the representationist presupposition dominant in this area. From this point of view, the informational turn in philosophy would not provide any great novelty, given that since the earliest days philosophical approaches to the nature of mind have always been mainly representationist. The novelty would not lie specifically in the Turing thesis, but in reflections on the nature of information, especially ecological information, and its relation to action.

Analisamos o conceito de informação a partir da hipótese de Adams em The informational turn in Philosophy, segundo a qual ocorreu na década de 1950 “uma virada de grande abrangência na Filosofia” com a publicação do artigo de Turing “Computing Machinery and Intelligence”. Adams sustenta que novos rumos estariam sendo delineados na pesquisa filosófica tendo como base o conceito de informação no tratamento de questões clássicas, tais como o problema da relação mente-corpo, percepção-ação, a natureza do conhecimento, dentre outros. Concordando parcialmente com Adams, julgamos, entretanto, que sua hipótese enfrenta dificuldades, sendo a mais fundamental delas concernente aos diversos significados atribuídos ao termo “informação”. Argumentamos que ainda que o conceito de informa- ção subjacente à proposta mecanicista de Turing, segundo a qual “pensar é computar”, esteja sendo empregado na Filosofia, isso ocorre não por seu teor mecanicista, mas, principalmente, pelo pressuposto representacionista vigente nessa área. Nesse sentido, a virada informacional na Filosofia não seria inovadora, uma vez que desde os seus primórdios a reflexão filosófica sobre a natureza da mente se apoia no pressuposto representacionista. A novidade residiria não especificamente na proposta de Turing, mas nas reflexões sobre a natureza da informação, especialmente da informação ecológica, e de sua relação com a ação.
The informational turn in Philosophy: any novelty in the study of Mind?